Distribution of zinc in vineyard areas treated with zinc containing phytopharmaceuticals - Bukovac, Vesna (Acta chimica slovenica, 2000)
Zinc concentration in vineyard soil is, in general, increased markedly by the long term application of zinc containing fungicides. The most significant source of Zn are nowadays dithiocarbamate based fungicides, e.g. Antracol. The concentration of total zinc and EDTA and ammonium lactate (AL) extractable Zn in soils are evaluated together with the concentration of Zn in different inorganic fertilizers and in fungicides. the results of the study indicate in the observed vineyard areas a long term accumulation of zinc appears. The study was made in vineyards of Kalvarija and Meranovo (Maribor, Slovenia)_
Keywords: cink; ditiokarbamati; ecology; ekologija; fitofarmacevtski pripravki; fungicidi; prst; vinogradi; vinogradništvo